Full-Wave Analysis of Ultrahigh Electromechanical Coupling Surface Acoustic Wave Propagating Properties in a Relaxor Based Ferroelectric Single Crystal/Cubic Silicon Carbide Layered Structure. (16th October 2017) - Ji, Xiaojun; Xiao, Qiang; Chen, Jing
Abstract : This paper describes a full-wave analysis of ultrahigh electromechanical coupling surface acoustic wave (SAW) of Y-cut X propagating Pb(In1/2 Nb1/2 )O3 -Pb(Mg1/3 Nb2/3 )O3 -PbTiO3 (YX-PIMNT) single crystals on a cubic silicon carbide (3C-SiC) substrate. There are several eigenmodes including shear horizontal (SH) and Rayleigh SAWs. Based on the finite-element method (FEM), the phase velocity (v p ) and coupling factor (K 2 ) of SAWs varying with the top electrode thickness, thickness, and Euler angle (θ ) of the YX-PIMNT substrate have been investigated. K 2 of SH SAW can reach an extremely high value of 75.9%. The proper control of structural parameters can suppress unwanted responses caused by other modes without deteriorating the coupling factor. The large K 2 value of SH SAW and suppression of unwanted responses have highly promising applications in developing ultrawideband and tunable SAW filters. Finally, the performance of 3C-SiC and 6H-SiC as substrates was investigated, and 3C-SiC was identified as a more attractive substrate candidate than 6H-SiC.